Effect of blue light plus chlorhexidine therapy on Streptococcus mutans biofilm and its regrowth in an in vitro orthodontic model - Panariello, Beatriz H.D.; Cavichioli, Eder A.M. [UNESP]; Sochacki, Sabrina Feitosa; Gandini Junior, Luiz Gonzaga [UNESP]; Duarte, Simone (Elsevier, 2022)
Introduction: Fixed orthodontic appliances create areas of stagnation for dental biofilms and make it difficult to clean the teeth; therefore, there is a risk of developing incipient caries lesions during the orthodontic treatment. The objective of this study is to determine if the combination of 2 different therapies, phototherapy by blue light (BL) and the antimicrobial 0.12% chlorhexidine (CHX) on enamel, orthodontic brackets, and elastics, would reduce or inhibit mature Streptococcus mutans biofilms and their regrowth on these substrates 24 hours after the application of the treatment; and if this treatment would interfere with bracket adhesion to the enamel. Methods: Biofilms of S. mutans UA159 were formed for 5-days over samples composed of a bovine enamel, orthodontic bracket, and orthodontic elastic. Then, the specimens were treated with 0.89% NaCl for 1 minute, BL for 12 minutes (72 J/cm2), 0.12% CHX for 1 minute, and BL for 12 minutes, followed by 0.12% CHX for 1 minute (BL+CHX). Biofilm was evaluated by colonies forming units and dry weight immediately after treatments and 24 hours after treatments (regrowth). The pH of the spent media was measured on the fifth and sixth days. Biofilm formation on the samples after the treatments and regrowth was visually evaluated by confocal laser scanning microscopy. Shear bond strength (SBS) between bracket and enamel was evaluated using a universal testing machine at a crosshead speed of 1 mm/min. After bonding, specimens were thermocycled (500× at 5-55°C), treated, and thermocycled again. Results: After 5 days of biofilm formation, BL+CHX significantly reduced the bacterial viability on enamel compared with NaCl (P = 0.004) and BL (P = 0.014). For bracket and elastic, all the treatments resulted in similar bacterial viability (P ≥0.081). In the regrowth, CHX and BL+CHX significantly reduced the bacterial viability in the enamel compared with the NaCl (P ≤0.015) and BL (P ≤0.013). For bracket, BL+CHX significantly reduced the bacterial viability compared with NaCl (P = 0.008) and BL (P = 0.009). For the elastic, BL+CHX eliminated the biofilms from the substrate. CHX and BL+CHX significantly reduced the bacterial viability 24 hours after treatment for all substrates (P ≤0.05). The media pH significantly increased when samples were treated with CHX and BL+CHX (P ≤0.001). Confocal laser scanning microscopy images visually showed an abundant quantity of red cells in the samples treated with BL+CHX. There was no difference in the SBS between the treatments (P ≥0.932). Conclusions: The association between BL and CHX reduced S. mutans biofilm and its regrowth on an in vitro orthodontic model and did not influence the bonding strength between bracket and enamel.